PENERAPAN MODEL PEMBELAJARAN STRUCTURED INQUIRY PADA MATERI HUKUM NEWTON UNTUK MENINGKATKAN HASIL BELAJAR PADA SISWA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Science learning that remains one-directional causes students' active involvement in constructing knowledge to be less than optimal, resulting in low conceptual understanding and Science Process Skills. This study aims to improve student learning outcomes on Newton's Laws material through the implementation of the Structured Inquiry learning model. A quantitative Pre-Experimental method with a One-Group Pretest-Posttest Design was employed, involving 34 seventh-grade students at the junior high school level. Data were collected through learning outcome tests and an ARCS model motivation questionnaire, then analyzed using N-Gain calculations and the Wilcoxon test. The findings indicate that the majority of students achieved either a high or moderate N-Gain category, with no students falling into the low category. The Wilcoxon test confirmed a significant difference between pretest and posttest scores, and student learning motivation as a whole was classified as excellent. Therefore, the Structured Inquiry learning model is proven effective in improving both student learning outcomes and motivation, as it provides opportunities for students to construct their own knowledge through guided and systematic inquiry steps.